CORPORATE GOVERNANCE AND FINANCING RISK OF SHARIA BANK IN INDONESIA - Muis Zunanto; Agung Abdullah (Journal of Management and Islamic Finance, 2023)
This study aims to examine the influence of Islamic bank governance on the financing risk of Islamic Commercial Banks in Indonesia. Sharia bank governance is proxied by the variables of the board of commissioners, audit committee, and sharia supervisory board (SSB). This study used panel data of Islamic commercial banks from 2015 to 2020 using purposive sampling. The data analysis technique used panel data regression through a fixed effect model. The test results show that the audit committee variable has a significant negative effect on the financing risk of Islamic commercial banks. Meanwhile, the board of commissioners and the SSB of the bank have no effect on the financing risk of Islamic commercial banks.